Oral Microbial Translocation Genes in Gastrointestinal Cancers: Insights from Metagenomic Analysis - Linqi Wang; Qinyu Wang; Yan Zhou (Microorganisms)
Along with affecting oral health, oral microbial communities may also be endogenously translocated to the gut, thereby mediating the development of a range of malignancies in that habitat. While species-level studies have proven the capability of oral pathogens to migrate to the intestine, genetic evidence supporting this mechanism remains insufficient. In this study, we identified over 55,000 oral translocation genes (OTGs) associated with colorectal cancer (CRC) and inflammatory bowel disease (IBD). These genes are primarily involved in signal transduction and cell wall biosynthesis and show consistency in their functions between IBD and CRC. Furthermore, we found that Leclercia adecarboxylata, a newly discovered opportunistic pathogen, has a significantly high abundance in the gut microbiota of colorectal cancer patients. OTGs of this pathogen were enriched in 15 metabolic pathways, including those associated with amino acid and cofactor metabolism. These findings, for the first time, provide evidence at the genetic level of the transfer of oral pathogens to the intestine and offer new insights into the understanding of the roles of oral pathogens in the development of gastrointestinal cancers.